Achievement gaps and correlates of early mathematics achievement: Evidence from the ECLS K—first grade sample. Vol. 13 No. 46 - Chatterji, Madhabi (Education Policy Analysis Archives, 2005)
In light of the NCLB Act of 2001, this study estimated mathematics achievement gaps in different subgroups of kindergartners and first graders, and identified child- and school-level correlates and moderators of early mathematics achievement. A subset of 2300 students nested in 182 schools from the Early Childhood Longitudinal Study K-First Grade data set was analyzed with hierarchical linear models. Relative to school mean estimates at the end of kindergarten, significant mathematics achievement gaps were found in Hispanics, African Americans and high poverty students. At the end of Grade 1, mathematics gaps were significant in African American, high poverty, and female subgroups, but not in Hispanics. School-level correlates of Grade 1 Mathematics achievement were class size (with a small negative main effect), at-home reading time by parents (with a large positive main effect) and school size (with a small positive main effect). Cross-level interactions in Grade 1 indicated that schools with larger class and school sizes had a negative effect on African American children's math scores; schools giving more instructional time to reading and math had a positive effect on high poverty students' scores, and schools with higher elementary teacher certification rates had a positive effect on boys' mathematics achievement.